SOUNDING ISLAM IN CONTEMPORARY INDONESIA: The Transformation of Javanese Tembang (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
This article examines the relationship between sound and religion focusing on mediated religion and the transformation of sonic sensation. It studies a Javanese children’s song (tembang dolanan) called Ilir-Ilir (Javanese pronunciation: [iler iler]) which is an example of a Javanese song bearing a deep philosophy, richness of interpretations, and modes of presentation. Examining the Javanese song Ilir-ilir, this paper examines the two dimensions of the song and the transformation of tembang dolanan into the Islamic ones through the meaning-making and sonic dimension to generate Islamic sensation. The analysis goes beyond the textual tradition -in case of the song i.e., lyrics and textual dimension of the song- as looking at the interpretation of the song and the sonic atmosphere of sound. The article further argues that the transformation Javanese Ilir-ilir delivers an important insight of relationship between sound and religion as to which sound contributes to the making of religious sensation and reverberates the mediated religion through sensational form.